The Impact of Energy Internet Enterprise Construction on Power Grid Business Organization Mechanism. Issue 1 (July 2021) - He, Mingjun; Zhang, Penghui; Liu, Shuxiao
Abstract: The construction of Energy Internet enterprises by power grid enterprises is a key decision for power grid enterprises to grasp the major strategic opportunities, and a key measure for power grid enterprises to deeply understand the internal and external strategic situation and continuously lead of the transformation and development of energy and power. As the core measure, the construction of operation mechanism of power grid business organization needs to clearly study and judge the external environmental factors' new situation, new influence and new requirements faced by the construction of Energy Internet enterprises such as policies, market, technology, so as to deeply grasp the opportunities and challenges faced by the construction of Energy Internet enterprises.